2010
DOI: 10.1016/j.whi.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Adherence and Test Performance on the Cost-Effectiveness of Cervical Cancer Screening in Developing Countries

Abstract: Objective-We examined the impact of patient adherence and screening test performance on the cost-effectiveness of visual inspection with acetic acid (VIA) and Pap smears when used with colposcopy for diagnosis.Materials and Methods-Cost-effectiveness analysis was performed using computer modeling. The primary outcome was cancer prevalence in the ten years following screening. Three hypothetical populations of 35-year-old women were compared: never-screened women, women screened with VIA, and women screened wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…For example, a study in Honduras comparing adherence rates after screening with either Pap smears or visual inspection with acetic acid (VIA) found that only 38% of women with abnormal Pap results adhered to recommended follow-up versus 84% of women with abnormal VIA results. [18] A major strength of our study is that it pinpoints the exact step during which the majority of women did not continue their recommended follow-up. Since 62% of women were lost between receiving their abnormal Pap result and scheduling a follow-up colposcopy, the MOH had sufficient evidence to implement a direct referral system between the primary health units where women obtain their results and the nearest hospital where colposcopy services are provided.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in Honduras comparing adherence rates after screening with either Pap smears or visual inspection with acetic acid (VIA) found that only 38% of women with abnormal Pap results adhered to recommended follow-up versus 84% of women with abnormal VIA results. [18] A major strength of our study is that it pinpoints the exact step during which the majority of women did not continue their recommended follow-up. Since 62% of women were lost between receiving their abnormal Pap result and scheduling a follow-up colposcopy, the MOH had sufficient evidence to implement a direct referral system between the primary health units where women obtain their results and the nearest hospital where colposcopy services are provided.…”
Section: Discussionmentioning
confidence: 99%
“…HPV vaccination offers protection against the development of cervical cancer and associated morbidities and mortalities, and is especially valuable in resource-limited settings where secondary prevention methods such as cytology screening are not widely available and may not be a cost-effective [25]. Recent work focusing on HPV vaccine acceptability in resource-limited settings including Kenya, Tanzania, Uganda, Latin America, the Caribbean, Vietnam, Malaysia, China, and India have generally found high acceptability of HPV vaccines [26][30].…”
Section: Introductionmentioning
confidence: 99%
“…VIA has proven to be feasible in low‐resource settings because of the simplicity and acceptance of this strategy, leading to increased adherence compared with cytology‐based screening . A CEA from Honduras found that VIA would cost $3198 per cancer case avoided compared with $36,802 with cytology‐based screening .…”
Section: Improving CC Control In Lamentioning
confidence: 99%